Adding a C-terminal Cysteine (CTC) Can Enhance the Bactericidal Activity of Three Different Antimicrobial Peptides - Chen, Heng-Li; Su, Pei-Yi; Kuo, Shu-Chen; Lauderdale, Tsai-Ling Y.; Shih, Chiaho (Frontiers in Microbiology, 2018)
The emergence of antibiotic-resistant bacteria has threatened our health worldwide. There is an urgent need for novel antibiotics. Previously, we identified a novel 37-mer antimicrobial peptide, HBcARD, with broad spectrum antimicrobial activity. Here, we improved the efficacy of HBcARD, by re-engineering the peptide, including the addition of a new cysteine to its C-terminus (CTC). The new 28-mer derivative, D-150-177C, contains all D-form arginines, in addition to a C-terminal cycteine. This peptide can kill antibiotic-resistant clinical isolates of Gram-negative bacteria, and is more potent than the parental HBcARD peptide in a mouse sepsis model. In another lung infection mouse model, D-150-177C showed protection efficacy against colistin-resistant A. baumannii. Unlike colistin, we observed no acute toxicity of D-150-177C in vivo. Interestingly, we found that CTC modification could enhance the antibacterial activity of several other antimicrobial peptides, such as buforinII and lysin. The potential application and mechanism of this CTC method as a general approach to improving drug efficacy, warrants further investigation in the future.